Exploring potential polysaccharide utilization loci involved in the degradation of typical marine seaweed polysaccharides by Bacteroides thetaiotaomicron - Yu, Biao; Lu, Zheng; Zhong, Saiyi; Cheong, Kit-Leong (Frontiers in Microbiology, 2024)
The research on the mechanism of marine polysaccharide utilization by Bacteroides thetaiotaomicron has drawn substantial attention in recent years. Derived from marine algae, the marine algae polysaccharides could serve as prebiotics to facilitate intestinal microecological balance and alleviate colonic diseases. Bacteroides thetaiotaomicron, considered the most efficient degrader of polysaccharides, relates to its capacity to degrade an extensive spectrum of complex polysaccharides. Polysaccharide utilization loci (PULs), a specialized organization of a collection of genes-encoded enzymes engaged in the breakdown and utilization of polysaccharides, make it possible for Bacteroides thetaiotaomicron to metabolize various polysaccharides. However, there is still a paucity of comprehensive studies on the procedure of polysaccharide degradation by Bacteroides thetaiotaomicron. In the current study, the degradation of four kinds of marine algae polysaccharides, including sodium alginate, fucoidan, laminarin, and Pyropia haitanensis polysaccharides, and the underlying mechanism by Bacteroides thetaiotaomicron G4 were investigated. Pure culture of Bacteroides thetaiotaomicron G4 in a substrate supplemented with these polysaccharides were performed. The change of OD600, total carbohydrate contents, and molecular weight during this fermentation were determined. These results were further consolidated by the genomic sequencing and bioinformatic analysis with the intention of revealing the mechanisms beneath them. Specifically, the Gene Ontology (GO) annotation, Clusters of Orthologous Groups (COG) annotation, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment were conducted to uncover the potential target genes and pathways. Several PULs were anticipated to participate in the breakdown of these four polysaccharides. These findings may help to understand the interactions between these marine seaweed polysaccharides and gut microorganisms.